Control Strategy for MMC Based on Super-Capacitor Energy Storage - Lei LI; TAO Jun; Mingxing ZHU; Yuan FAN (Zhongguo dianli)
In order to resolve the problems of the rapid variation of power system’s active power caused by grid-integrated renewable energy and pulsed loads, which will threaten the stability of adjacent generator units and power systems, a distributed energy storage system is proposed based on the modular multilevel converter (MMC) integrated with super-capacitor energy storage. The bi-directional DC/DC converters are used to control the charge and discharge process of the energy storage system, and the design principles for relevant parameters are provided. The control strategy based on dual-closed-loop PI regulator and the phase shifted PWM technology is used to control the balance of super-capacitor energy and the capacitor voltage stability of the MMC sub-modules. The energy management mechanism is introduced to control the collaborative operation of the MMC and the DC/DC converters, subsequently realizing the real-time compensation for pulsed active power variation in medium- and high-voltage systems. The simulation results with Matlab/Simulink platform have verified the effectiveness of the proposed device and control strategy.